Perkembangan Hukum Keluarga Islam Di Asia Selatan: Studi Komparatif Di Negara Pakistan, India, Dan Bangladesh: The Development of Islamic Family Law in South Asia: A Comparative Study of Pakistan, India and Bangladesh - Muhammad Iqbal Hanafi Nasution; Juni Arnisa Napitupulu; Uswatun Hasanah; Ibnu Radwan Siddik Turnip; Rahmad Efendi (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the development of Islamic family law in South Asia, particularly in Pakistan, India, and Bangladesh, through a normative review of the main regulations that shape the family law system in the region. The study focuses on the influence of colonial heritage, national legal politics, and patterns of Sharia interpretation on the direction of Islamic family law reform. The method used is normative jurisprudence with a statute approach, through an examination of regulations such as the Muslim Personal Law (Sharia) Application Act 1937, the Muslim Family Laws Ordinance 1961, and the Muslim Marriages and Divorces (Registration) Act 1974. The data was analyzed qualitatively to identify differences in normative configurations between countries. The results of the study show that although the three countries have similar fiqh roots, the approach to Islamic family law legislation has developed differently. Pakistan stands out with administrative reforms that strengthen the role of the state, Bangladesh combines formal regulations with community mediation mechanisms, while India maintains a personal law system with limited state intervention. This study concludes that the effectiveness of Islamic family law in South Asia depends on the synergy between state codification and community authorities oriented towards substantive justice and social welfare.